The upper lithostratigraphic unit of ANDRILL AND-2A core (Southern McMurdo Sound, Antarctica): local Pleistocene volcanic sources, paleoenvironmental implications and subsidence in the southern Victoria Land Basin - DEL CARLO P.; PANTER K.; BASSETT K.; DI VINCENZO G.; BRACCIALI, LAURA; ROCCHI, SERGIO (Global and Planetary Change, 2009)
We report results from the study of the uppermost 37 m of the Southern McMurdo Sound (SMS) AND-2A drill core, corresponding to the lithostratigraphic unit 1 (LSU 1), the most volcanogenic unit within the core. We present data on the age, composition, volcanological and depositional features of the volcanic sedimentary and tephra deposits of LSU 1 and discuss their source, mechanisms of emplacement and environment of deposition. Sedimentary features and compositional data indicate shallow water sedimentation for the whole of LSU 1. Most of LSU 1 deposits are a mixture of near primary volcanic material with minor exotic clasts; derived from the Paleozoic crystalline basement rocks. Among volcanic materials, glassy particles are the most abundant. They were produced by mildly explosive basaltic eruptions occurring in subaerial and subaqueous environments. The Dailey Islands group. 13 km south-southwest of the SMS drill-site, has been identified as a possible source for the volcanics on the basis of similarity in composition and age. (40)Ar-(39)Ar laser step-heating analyses on a lava sample from Juergens Island yields an age of 775 +/- 22 ka. Yet because of the minimal reworking features of vitriclasts, preservation of fragile structures in volcaniclastic sediments and evidence for volcanic seamounts to the north of the Dailey Islands, it is likely that some of the material originated also from vents close to the drill-site. Evidence for local volcanic sources and for deposition of sediments in a shallow marine environment provides indications about the local paleogeography and implications for the subsidence history of the southern Victoria Land Basin from Pleistocene to Recent.